2010
DOI: 10.1016/j.jaci.2010.05.042
|View full text |Cite
|
Sign up to set email alerts
|

Man's best friend? The effect of pet ownership on house dust microbial communities

Abstract: Capsule Summary Pet-ownership, which has been shown to be protective against allergic disease development, is associated with increased house dust bacterial diversity and fewer fungal species, suggesting a potentially microbial-based mechanism for this protective effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
181
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 219 publications
(191 citation statements)
references
References 12 publications
7
181
0
3
Order By: Relevance
“…This is consistent with our previous study in which NP dust samples exhibited low bacterial burden, with 40% of samples failing to produce a 16S rRNA PCR product (12). Nonmetric multidimensional scaling (NMDS) analysis based on a Canberra distance matrix confirmed that the microbial composition of the D dust used for these experiments was more similar to indoor/ outdoor dog-associated dust samples than to any other type of house dust (cat-owning or no-pet homes) examined in our previous study (12) (Fig. S1A).…”
Section: Resultssupporting
confidence: 93%
“…This is consistent with our previous study in which NP dust samples exhibited low bacterial burden, with 40% of samples failing to produce a 16S rRNA PCR product (12). Nonmetric multidimensional scaling (NMDS) analysis based on a Canberra distance matrix confirmed that the microbial composition of the D dust used for these experiments was more similar to indoor/ outdoor dog-associated dust samples than to any other type of house dust (cat-owning or no-pet homes) examined in our previous study (12) (Fig. S1A).…”
Section: Resultssupporting
confidence: 93%
“…That this process depends on microbial exposures is further supported by our recent findings that dog ownership, which has previously been associated with protection against allergic disease development, is associated with a significant increase in house dust bacterial diversity and lower fungal richness, compared to homes with no pets. 22 Moreover, although the numbers were small in this study, the microbial composition of the house dust could largely be differentiated on the basis of pet behavior. House dust from homes with pets (dogs or cats) who were permitted both in-and outdoors were associated with a diverse array of bacterial species similar across all samples and averaged at about 1,146 taxa ± 125.…”
Section: Probiotic Manipulation Of the Gastrointestinal Microbiotamentioning
confidence: 75%
“…[12][13][14][15][16] The mechanisms that drive this protective effect are not understood. 17,18 However, it has been shown that the early life intestinal microbial community, which we and others hypothesize may be impacted by household dogs' influence on the environmental microbiome, 19,20 may alter immune responses and thereby promote tolerance to common allergens in contrast to allergic sensitization.…”
mentioning
confidence: 80%